Pseudo-precocious puberty secondary to Juvenile Granulosa cell tumour in a 30-month-old female toddler: A case report - Taiwo Oni; Adesola Adekoya; Grillo Elizabeth; John Nwadiokwu; Victor Okebalama; Oluwaseun Anifowose (Babcock University Medical Journal)
Background: Precocious puberty is rare globally and its incidence in Nigeria is unknown, as few reported cases exist.